2002
DOI: 10.1046/j.1532-5415.2002.50605.x
|View full text |Cite
|
Sign up to set email alerts
|

Change in Muscle Strength Explains Accelerated Decline of Physical Function in Older Women With High Interleukin‐6 Serum Levels

Abstract: Older women with high IL-6 serum levels have a higher risk of developing physical disability and experience a steeper decline in walking ability than those with lower levels, which are partially explained by a parallel decline in muscle strength.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
342
0
21

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 552 publications
(381 citation statements)
references
References 17 publications
18
342
0
21
Order By: Relevance
“…This association may be attributable to a direct effect of IL-6 on muscle atrophy and/or to the pathophysiologic role of IL-6 in specific diseases. However, we could only partially confirm strong associations of IL-6 with physical performance (SPPB) in aged populations (Cesari et al 2004;Cohen et al 1997;Ferrucci et al 2002;Tiainen et al 2010). Additionally, no association with IL-6 was found with the age-related loss of muscle strength and function in our communitydwelling oldest old (data not shown).…”
Section: Inflammatory Associations With Individual Aspects Of Functiomentioning
confidence: 56%
“…This association may be attributable to a direct effect of IL-6 on muscle atrophy and/or to the pathophysiologic role of IL-6 in specific diseases. However, we could only partially confirm strong associations of IL-6 with physical performance (SPPB) in aged populations (Cesari et al 2004;Cohen et al 1997;Ferrucci et al 2002;Tiainen et al 2010). Additionally, no association with IL-6 was found with the age-related loss of muscle strength and function in our communitydwelling oldest old (data not shown).…”
Section: Inflammatory Associations With Individual Aspects Of Functiomentioning
confidence: 56%
“…Until today, only a limited number of prospective population studies further reported on the positive association between IL-6 and physical decline in older individuals. However, these previous studies were all restricted to lower age categories (Ferrucci et al 2002;Schaap et al 2009;Penninx et al 2004;Stenholm et al 2010;Taaffe et al 2000), highfunctioning persons (Schaap et al 2009;Penninx et al 2004;Taaffe et al 2000;Ferrucci et al 1999), or longer follow-up periods (Schaap et al 2009;Stenholm et al 2010;Taaffe et al 2000;Ferrucci et al 1999) or were gender-specific (Ferrucci et al 2002). Therefore, the generalizability of these findings in the oldest old might be limited.…”
Section: Discussionmentioning
confidence: 96%
“…However, independent of the cohort and the equipment used, the proposed cutoffs are quite similar. The WHAS study proposed a cutoff of 3.1 pg/ml (Ferrucci et al 2002), Harris and coworkers of 3.2 pg/ml , and Ferrucci and coworkers of 2.5 pg/ml . Following a similar cutoff score of 2.98 pg/ml, inflammageing was apparent with 31.6 % of our participants having IL-6 values above the cutoff value.…”
Section: Gds Decline N=316mentioning
confidence: 99%
“…A comparison of unadjusted means shows that all participants (both elderly men and women) in the highest tertile of CZr had significantly lower BMI, cholesterol and albumin, higher incidence of congestive heart failure, higher IL-6, and CRP levels as well as worse in physical and functional performance than those observed in the lower tertiles at baseline. An adjustment for inflammatory parameters (IL-6 and CRP) affects the association of CZr with baseline physical and functional measures, thus limiting the relevance of CZr as biomarker of physical and functional status in comparison with other well-known inflammatory biomarkers (Brinkley et al 2009;Ferrucci et al 2002). However, the association between CZr and physical decline shows that CZr levels are significantly associated with the worsening of physical performance in a 2-year follow-up.…”
Section: Discussionmentioning
confidence: 99%